A comprehensive study of phrotic mites (Acari: Mesostigmata) related to bark beetles in Northern Turkey, introducing new findings - Cılbırcıoğlu, Cihan (Springer Science and Business Media LLC, 2025)
Abstract
In the Kastamonu forests of Turkey's Black Sea Region, researchers collected 11 mite species from the Mesostigmata group associated with Ips sexdentatus (Börner), Ips acuminatus (Gyllenhal), and Tomicus piniperda (Linnaeus) (Coleoptera: Curculionidae, Scolytinae), as well as within their galleries. Among these, species such as Ameroseius longitrichus Hirschmann, 1963; Cercoleipus kuznetsovi Khaustov, 1997; Dendrolaelaps quadrisetosimilis Hirschmann, 1960; Dendrolaelaps quadrisetus Berlese, 1920; Hypoaspis maryamae Joharchi & Halliday, 2011; Lasioseius ometes Oudemans, 1903; Pleuronectocelaeno barbara Athias-Henriot, 1959; Proctolaelaps hystrix Vitzthum, 1923; Schizocyrtillus rarus Khaustov, 2000 and Stratiolaelaps scimitus Womersley, 1956 were reported for the first time in Turkey.